2020
DOI: 10.1093/ppmgov/gvz026
|View full text |Cite
|
Sign up to set email alerts
|

Democratic Backsliding, Populism, and Public Administration

Abstract: What happens to public administration when populists are elected into government? This article argues that populists seek to realize an anti-pluralist reform agenda, thereby fuelling trends of democratic backsliding. Against this background, the article discusses potential goals and strategies of populist public administration policy and introduces examples of how populists sought to capture (Orbán in Hungary), dismantle (Fujimori in Peru), sabotage (Trump in the United States), and reform (Blocher in Switzerl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 41 publications
1
57
0
6
Order By: Relevance
“…Based on their assessment, the authors show that the dismantling of environmental governance in Brazil is not merely rhetorical, but a political tactic meant to legitimize the promotion of "total extractivism" while maintaining a populist appeal. At the same time, the article provides important insights to understand the sequencing of institutional dismantling performed by populists in government office and witnessed in other world regions (Bauer and Becker 2020).…”
Section: Contributions Of the Special Sectionmentioning
confidence: 99%
“…Based on their assessment, the authors show that the dismantling of environmental governance in Brazil is not merely rhetorical, but a political tactic meant to legitimize the promotion of "total extractivism" while maintaining a populist appeal. At the same time, the article provides important insights to understand the sequencing of institutional dismantling performed by populists in government office and witnessed in other world regions (Bauer and Becker 2020).…”
Section: Contributions Of the Special Sectionmentioning
confidence: 99%
“…Organisations such as Freedom House and the Economist Intelligence Unit that classify political systems have been documenting a general decline in democracy over the past decade at least. Likewise, scholars have been documenting that decline and its implications for governance and the public bureaucracy (Bauer et al, 2021).…”
Section: The Mount Everest Reasonmentioning
confidence: 99%
“…Processes within the administrations and their relationship vis-à-vis the political majorities after 2004, in turn, were covered to a lower degree. Early on, studies demonstrated the potential of such studies for better understanding domestic political tectonics (Grzymała-Busse 2003) and also recent analyses have suggested exploring the role of public administrations in backsliding processes (Bauer and Becker 2020).…”
Section: Conclusion Open Questions and Future Researchmentioning
confidence: 99%